1983
DOI: 10.1002/tea.3660200905
|View full text |Cite
|
Sign up to set email alerts
|

Children's conceptions of the changes of state of water

Abstract: Children are very familiar with water, ice, and steam as these things have been part of their lives since they first crawled into the kitchen. In this study children's conceptions about familiar phenomena associated with water, e.g., evaporating, condensing, boiling, and the melting of ice, were investigated using a clinical interview technique. The prevalence of specific views at particular age levels was also studied. The results of the investigation indicate that children do have ideas about the changes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
206
0
37

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(253 citation statements)
references
References 11 publications
10
206
0
37
Order By: Relevance
“…In accordance with previous studies (e.g., Osborne & Cosgrove, 1983;Tytler, 2000;Johnson, 1998bJohnson, , 1998c, representative responses were ' the water is absorbed by the sun ', ' the plate absorbs the water ', ' the heat absorbs the water ' or 'the water does not exist anymore '. However, a number of pupils' responses such as 'the water has been transformed into a gas and it left the plate ...' was considered 'sufficient', while an answer such as 'the water becomes small drops and goes up in the air' was considered 'intermediate'.…”
Section: Resultssupporting
confidence: 87%
“…In accordance with previous studies (e.g., Osborne & Cosgrove, 1983;Tytler, 2000;Johnson, 1998bJohnson, , 1998c, representative responses were ' the water is absorbed by the sun ', ' the plate absorbs the water ', ' the heat absorbs the water ' or 'the water does not exist anymore '. However, a number of pupils' responses such as 'the water has been transformed into a gas and it left the plate ...' was considered 'sufficient', while an answer such as 'the water becomes small drops and goes up in the air' was considered 'intermediate'.…”
Section: Resultssupporting
confidence: 87%
“…Some such students consider that molecules are in substances, rather than that substances consist of molecules, and believe something to be between the molecules. Osborne and Cosgrove (1983) found that 8-17-year-old students in New Zealand knew little about the particulate nature of matter. With little knowledge or an alternative understanding about the particulate nature of matter, students might not understand that a chemical equation represents a chemical reaction involving atom rearrangement and bond breaking and formation (Krajcik, 1991).…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…The instrument was synthesized by selected items/questions, which have been used to access students' knowledge on this specific domain in a number of research studies (Johnson, 1998a, b, c;Osborne, & Cosgrove, 1983;Author 3, Author 2 et al, 2008). In particular, it was especially based on an extended and more elaborated version of the instrument used by The first 3 items (1A, 1B, and 1C) concern the solid state.…”
Section: Pupils' Achievement Concerning Their Understanding Of the Pmentioning
confidence: 99%
“…As far as the changes of state are concerned, Osborne and Cosgrove (1983) investigated students' perceptions by interviewing forty-three school pupils ranging in age from eight to seventeen years. The findings were consolidated by means of a paper-pencil survey technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation